Post-exercise heart rate variability : a new approach to evaluation of exercise-induced physiological training load - Kaikkonen, P. (Studies in Sport, Physical Education and Health, 224, 2015)
To improve maximal endurance performance, an optimal physiological training load, i.e. the balance between exercise and recovery, is required. In general, the goal of a single endurance exercise session is to transiently disturb body homeostasis after which a so-called supercompensation, an improvement in performance, can occur if the recovery period is adequate. The physical training load of a single exercise session consists of the combination of exercise intensity and duration. At the present time, there is no single tool to quantify the amount of disturbance of homeostasis that is equal to physiological training load of a single exercise session. Heart rate variability (HRV), the changes in time between consecutive R-R -intervals, has widely been used as a non-invasive tool to estimate changes in cardiac autonomic modulation in different physiological conditions. Methodological limitations have usually inhibited the investigation of HRV during changes in autonomic modulation, for example during immediate recovery after exercise. In the present study, a time- frequency analysis of HRV was used to exceed this limitation. The main aim of the present study was to find out if HRV could be used to estimate the exercise- induced physiological training load of single endurance exercise sessions. The results of the present study indicated that the differences in physical training load of endurance exercise sessions, either by changes in exercise intensity or duration, could be detected in immediate post-exercise HRV already during the first recovery minutes. The main factor determining post-exercise HRV seemed to be exercise intensity, but increases in exercise duration could be detected in post-exercise HRV as well, if the exercise intensity was at least moderate. There were negative relationships between post-exercise HRV and so-called traditional training load parameters, for example blood lactate, rating of perceived exertion, excess post-exercise oxygen consumption and training impulse. The results of the present study suggest that immediate post-exercise HRV may be used to estimate physiological training load of single exercise sessions, and it seems to give additional information when compared to traditional parameters used to quantify training load.